CONTENT, METHODS, AND MEANS OF TEACHING ENGLISH THROUGH GAMIFICATION IN HIGHER EDUCATION - Shavkieva Dilfuza Shakarbaevna (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article discusses the sensory and emotional activity of mastering educational material in English, the ability to master the language, determine the level of development of competencies, create teaching aids, recommendations on the use of game technologies in mastering educational information and apply them in the educational process, analyze its effectiveness